HUBUNGAN INTENSITAS PENGGUNAAN MEDIA SOSIAL DENGAN TINGKAT KECEMASAN PADA MAHASISWA KEDOKTERAN UNIVERSITAS BAITURRAHMAH PADANG ANGKATAN 2021 - Aulia Nopriyanti; Ade Yuli Amellia; Laura Zeffira (Yayasan Nusantara Hasana Berdikari, 2024)
Social media is a form of advancement from technology that is widely used by people around the world including Indonesia which is used as a means of long-distance communication between one individual and another, Students are the group most vulnerable to anxiety. Excessive use of social media and pressure from the inside and outside will cause a bad impact on the body. Objective of this research to find out the relationship between the intensity of social media use and anxiety levels in Baiturrahmah University Medical students class of 2021. The scope of this research is mental medicine (psychiatry). The study was conducted in February - November 2022. This type of research is analytics. The affordable population in the study was 44 samples of Baiturrahmah University Medicine students with simple random sampling techniques. Univariate data analysis is presented in the form of a frequency distribution and bivariate analysis using the Spearman rho test, data processing using the SPSS computer program version IBM 25.0. The most age is 19 years old, namely 30 people (68.2%), the most gender is women, namely 32 people (72.7%), the most used social media accounts are WhatsApp, namely 22 people (50.0%), the intensity of social media use is normal, namely 24 people (54.5%), the most anxiety level is mild, namely 24 people (54.5%), and there is an association between the. The most age is 19 years old, the most gender is female, the most used social media account is WhatsApp, the most social media usage intensity is normal, the most anxiety level is mild, and there is a relationship between the intensity of social media use and anxiety levels in Baiturrahmah University Medical students class 2021.